Effects of phase inversion and rheological factors on formation of defect-free and ultrathin-skinned asymmetric polysulfone membranes for gas separation - Ismail, A. F.; Lai, P. Y. (Elsevier, 2003)
Development of defect-free and ultrathin-skinned asymmetric membranes for gas separation process without requiring any additional post-treatments such as curing or coating is a major breakthrough in membrane technology. Correlation of primary dry/wet phase inversion process with rheology aspects is a novel approach in membrane research that provides a potential platform to improve membrane performance. The former controls general morphology of membrane, whereas the latter further affects molecular orientation in membrane. Casting solution developed in this study consisted of polysulfone, tetrahydrofuran (THF), N,N-dimethylacetamide (DMAc) and ethanol (EtOH). The produced membranes were tested with hydrogen and nitrogen as test gases. Essentially defect-free and ultrathin skin layer was achieved for asymmetric polysulfone membranes. Selectivity of these membranes was relatively higher compared to conventional membranes, some of them even surpassed the intrinsic selectivity.